Agreement between the stages cycling and SRM powermeter systems during field-based off-road climbing - Hurst, H. T.; Atkins, S.; Sinclair, J.; Metcalfe, J. (Journal of Science and Cycling, 2015)
The aim of this study was to determine the agreement between two portable cycling powermeters for use doing field based mountain biking. A single participant performed 15 timed ascents of an off-road climbs. The participants bicycle was instrumented with Stages Cycling and SRM powermeters. Mean and peak power output and cadence were recorded at 1 s intervals by both systems. Significant differences were determined using paired t-tests, whilst agreement was determined using 95% ratio limits of agreement (LoA). Significant differences were found between the two systems for mean power output (p<.001), with the Stages powermeter under reporting power by 8 % compared to the SRM. LoA for mean power output were 0.92 ×÷ 1.02 (95% LoA = 0.90 - 0.93). Peak power output was also significantly lower with the Stages powermeter (p=.02) by 5 % when compared to the SRM powermeter. LoA for peak power output were 0.94 ×÷ 1.09 (95% limits of agreement = 0.87 - 1.03). Significant differences were found for mean cadence between the two powermeters (p=.009), with LoA being 0.99 ×÷ 1.01 (95% limits of agreement = 0.99 - 1.00). This study found that though the Stages Cycling powermeter provided a reliable means of recording power output and cadence, the system significantly underestimated mean and peak power output when compared with the SRM system. This may in part be due to differences in strain gauge configuration and the subsequent algorithms used in the calculation of power output and the potential influence of bilateral imbalances within the muscles may have on these calculations.